Pengaruh Penggunaan Media Zoom Cloud Meeting terhadap Peningkatan Hasil Belajar Alquran Hadits pada Masa Pandemi Covid-19 Siswa Kelas Iv Mi As’adiyah Bontang Tahun Pembelajaran 2020/2021 - Murni; Maghfiroh, Lailatul (NABAWI: Jurnal Penelitian Pendidikan Islam, 2025)
The online learning (distance learning) conducted by the teachers of MI As'adiyah Bontang for the subjects of Quran Hadith is by using Zoom Cloud Meeting media. The research problem formulated by the researcher is: "Is there an influence of using Zoom Cloud Meeting media on the improvement of learning results in the Quran Hadith during the Covid-19 pandemic for fourth-grade students of MI As'adiyah?" The purpose of this research is to determine whether there is an influence of using Zoom Cloud Meeting media on the improvement of learning results in the Quran Hadith during the Covid-19 pandemic for fourth-grade students of MI As'adiyah Bontang in the academic year 2020/2021. The research method used is quantitative research, and the data collection methods used by the researcher are observation, interviews, questionnaires, and documentation. The data analysis technique uses the Product Moment formula. The research results show the value of X and the value of Y based on the students' learning result sheets, with the result of the calculated r = 0.421, which is greater than the tabled r = 0.349 at a 5% significance level. Thus, there is an influence of using Zoom Cloud Meeting media on the improvement of learning results in the Quran Hadith, as known through the questionnaires distributed to the students. The hypothesis in this research shows a significant influence of using Zoom Cloud Meeting media on the improvement of learning results in the Quran Hadith, with the calculated t value being greater than the tabled t value (calculated t value is 2.57 > tabled t value of 2.042), therefore it can be accepted. The conclusion of this research is that there is an influence of using Zoom Cloud Meeting media on the improvement of learning results in the Quran Hadith during the Covid-19 pandemic for fourth-grade students of MI As'adiyah Bontang.